Genetical and ultrastructural aspects of the immotile-cilia syndrome. - Afzelius, B A (1981)
The immotile-cilia syndrome is a congenital disorder characterized by all cilia in the body being either immotile or showing an ineffective beating pattern. Most symptoms, not unexpectedly, come from the ciliated epithelia, but two further symptoms are: (1) male sterility caused by the spermatozoa being unable to swim progressively (the sperm tail has the same structure as a cilium), and (2) situs inversus in 50% of the cases possible caused by an inability of embryonic cilia to shift the heart to the left side. By electron microscopy, one can see directly which of the many ciliary components is the missing one. The molecular basis of this congenital defect can then be detected, and it has been found to be a heterogeneous disease. There are many genes that, when mutated, will cause the cilia to be dysfunctional or totally immotile. The fact that many genes may be responsible for the syndrome will also explain why it has a relatively high prevalence and why previous investigators have been unable to locate the (assumed single) gene by linkage analysis. The trait, situs inversus, is of particular interest as it occurs in only 50% of the assumed homozygotes. I conclude that the wild-type genes code for a control of the proper body asymmetry and the mutated ones for a lack of control, and, hence, to a random situs determination.